Classification of Mental Health Establishments in India According to Levels of Care: A Policy Perspective - Kannan Palaniyandi Ponnusamy; Panneerselvan C (Indian Journal of Psychological Medicine, 2026)
The recent classification of mental health establishments under the Mental Healthcare Act, 2017, is based largely on institutional affiliation. This viewpoint proposes a care-level–based classification comprising acute, intermediate, and rehabilitation services. Such an approach may better reflect clinical needs, support service planning, and align with the objectives of the Mental Health Care Act.